Aboveground biomass expansion factors for Pinus chiapensis (Mart.) Andresen - Chávez-Pascual, Edwin Yoshimar; Rodríguez-Ortiz, Gerardo; Carrillo-Rodríguez, José Cruz; Enríquez-del Valle, José Raymundo; Chávez-Servia, José Luis; Campos-Ángeles, Gisela Virginia (Revista Mexicana de Ciencias Agrícolas, 2018)
The biomass expansion factors (BEF) allow estimating the amount of biomass set per tree based on inventory variables; useful information for climate change projects. The objective was to estimate BEF variables per tree, through the generation of regression models for volume and aboveground biomass in Pinus chiapensis (Mart.) Andresen, in a community in the northern highlands of Oaxaca. Destructive sampling of 70 trees was made during 2012, randomly selecting individuals in proportion to the diametric frequency. The stem was cubed by the overlapping bolt method. The volume of wood with bark was transformed to biomass by the specific gravity and for the rest of the aboveground component were used conversion factors of biomass (dry weight / fresh weight). Nonlinear models of total volume and trade volume with and without bark and total aboveground biomass were obtained. Allometric variables were used from inventory like normal diameter (ND, cm) and total height (TH, m). For the elaboration of volumetric rates, adjusted models showed determination coefficients between 0.94 and 0.98. The Schumacher-Hall model showed the best fit for total aboveground biomass R2= 0.95, using the same independent variables from volume. The BEF was obtained by the quotient of the model from biomass and total tree volume with bark (BEFvtcc= 1040.771 x ND0.15073 x TH-0.42946). With this equation, it is possible to estimate reliably, the total aboveground biomass (kg) in trees of Pinus chiapensis from of inventory variables or volume.
Keywords: regression models; destructive sampling; specific gravity